Ligand-induced phosphorylation of the murine interleukin 3 receptor signals its cleavage. - Mui, A L (1992)
The murine interleukin 3 receptor (mIL-3R) is a heterodimer consisting of a 70-kDa alpha subunit and one of two alternative 120-kDa beta subunits termed beta IL-3 and beta c. beta IL-3 (originally called Aic2A) is capable of binding mIL-3 by itself, whereas beta c (Aic2B) does not bind any ligand on its own but increases the affinity of mIL-3, murine granulocyte/macrophage-colony-stimulating factor, and mIL-5 for their respective alpha subunits. Interestingly, although the mIL-3R does not possess tyrosine kinase activity, its beta IL-3 subunit does become tyrosine phosphorylated upon binding mIL-3. To further investigate the properties of this subunit, we have purified it from the cell line B6SUtA1, which expresses a high level of mIL-3R. Intriguingly, studies comparing the stability of the 140-kDa, tyrosine-phosphorylated form of this subunit with its 120-kDa, non-tyrosine-phosphorylated form reveal that the former is far less stable and is rapidly degraded to a 70-kDa fragment. Mixing experiments demonstrate that the differential stability of the two forms is due to an intrinsic difference in protease susceptibility. Phosphatase studies indicate that the higher protease susceptibility of the tyrosine-phosphorylated beta IL-3 is due to the presence of both phosphotyrosine and phosphoserine residues. Western analyses using an anti-N-terminal mIL-3R beta IL-3 chain antibody reveal that this proteolytic cleavage also occurs rapidly in intact cells following stimulation with mIL-3 and occurs at the cell surface, since it takes place within minutes at 37 degrees C, is observed with purified plasma membranes, and is not inhibited by chloroquine. This degradative step may play an important role in the mechanism of action of mIL-3.